Max & Ruby. Sharing & caring [videorecording (DVD)]. (Max & Ruby, 2015)
Max, a determined three-year-old bunny, and his big sister, Ruby, a smart, goal-oriented seven-year-old, offer an empowering message for children by showing Max and Ruby playing together and resolving their differences in ways that are respectful and supportive.